2014
DOI: 10.4274/tjh.2013.0011
|View full text |Cite
|
Sign up to set email alerts
|

Local Renin-Angiotensin System in Normal Hematopoietic and Multiple Myeloma-Related Progenitor Cells

Abstract: Objective: The prominent functions of the local renin-angiotensin system (RAS) in primitive hematopoiesis further support the hypothesis that local autocrine bone marrow RAS could also be active in neoplastic hematopoiesis. The aim of this study is to examine critical RAS elements in normal CD34+ hematopoietic stem cells and multiple myeloma (MM)-related progenitor cells.Materials and Methods: The study group comprised the total bone marrow cells (CBM) of 10 hematologically normal people, the CD34+ stem cell s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Moreover, there are limited data showing RBP-J gene mutations in leukemia patients [24,25]. Serum ACE was found increased in MM patients and local RAS components were also found in the following studies [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there are limited data showing RBP-J gene mutations in leukemia patients [24,25]. Serum ACE was found increased in MM patients and local RAS components were also found in the following studies [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…The overall results of the present data mining study reveal the complicated nature of MM [28] and locate the drug bortezomib at the critical crossroads of the pathobiology of the disease, driving the clinical course of MM. For instance, the LP-1 cell line was found to be resistant to bortezomib in our present study (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…We had initially indicated that there is a local hematopoietic bone marrow (BM) renin-angiotensin system (RAS), active in the physiological and pathological hematopoiesis (reviewed by Haznedaroglu and Beyazit [ 1 ]). Turkish Journal of Hematology has already published two critical research papers on the impact of the local BM RAS on the pathobiological course of neoplastic hematological disorders [ 2 , 3 ].…”
Section: To the Editormentioning
confidence: 99%